2018
DOI: 10.1186/s13048-018-0423-y
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent difference in impact of fertility preserving surgery on disease-specific survival in women with stage I borderline ovarian tumors

Abstract: BackgroundThis study was to determine age-specific impact of fertility preserving surgery on disease-specific survival in women with stage I borderline ovarian tumors (BOTs). Patients diagnosed during 1988–2000 were selected from The Surveillance, Epidemiology, and End Results (SEER) database. The age-specific impact of fertility preserving surgery and other risk factors were analyzed in patients with stage I BOTs using Cox proportion hazard regression models. Data from our hospital were collected during 1996–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…However, another study reported that there was no statistically significant difference between patients who underwent cystectomy or unilateral salpingo-oophorectomy [27]. A recent study involving 6295 patients showed that FSS was associated with worse DFS in patients aged ≥50 years than in those aged < 50 years [28]. Another study showed that surgical procedure (conservative vs. radical) was not an independent prognostic factor for DFS or OS [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that there was no statistically significant difference between patients who underwent cystectomy or unilateral salpingo-oophorectomy [27]. A recent study involving 6295 patients showed that FSS was associated with worse DFS in patients aged ≥50 years than in those aged < 50 years [28]. Another study showed that surgical procedure (conservative vs. radical) was not an independent prognostic factor for DFS or OS [12].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that there was no statistically significant difference between patients who underwent either cystectomy or unilateral salpingooophorectomy [25]. A recent study including 6295 patients showed that FSS was associated with worse disease-specific survival in patients ≥ 50 years of age, but not in those < 50 years of age [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that there was no statistically significant difference between patients who underwent cystectomy or unilateral salpingo-oophorectomy [25]. A recent study involving 6295 patients showed that FSS was associated with worse DFS in patients aged ≥50 years than in those aged <50 years [26]. Another study showed that surgical procedure (conservative vs. radical) was not an independent prognostic factor for DFS or OS [11].…”
Section: Discussionmentioning
confidence: 99%